Peran Pelatih sebagai Faktor Dominan Motivasi Latihan Siswa Persaudaraan Setia Hati Terate Kecamatan Bagor - Prasetyo, Moch. Rizal; Prasetyo, Moch.; Pratama, Budiman Agung; Harmono, Setyo (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to identify the role of the coach as a dominant factor in the motivation of pencak silat students of the Persaudaraan Setia Hati Terate (PSHT) in Bagor District, Nganjuk Regency. The study used a descriptive quantitative approach with a survey method. The research sample consisted of 57 active students from six training areas determined through a total sampling technique. Data collection was carried out using a Likert-scale questionnaire that had been tested for validity and reliability (Cronbach's Alpha = 0.932) through Google Form. Data were analyzed using descriptive percentage techniques using IBM SPSS Statistics version 26. The results showed that the role of the coach was the highest indicator in the extrinsic motivation dimension with a percentage of 92.28%, exceeding other indicators including family support (91.93%), training environment (89.30%), peer support (85.61%), peer influence (66.67%), and parental encouragement (61.05%). Overall, 66.7% of students were in the very high motivation category and 33.3% in the high category. These findings prove that the quality of coaching and the psychological approach of the trainer are the main keys to the sustainability of student participation in PSHT pencak silat training.